Variation of Acehnese Monophthong /ʌ/ in Western Acehnese Dialect - Tanzir Masykar; Roni Agusmaniza; Tabsyir Masykar; Huang Shan; Febri Nurrahmi (Journal of English Language Teaching and Linguistics, 2021)
Acehnese has many dialects, one of which is the western Acehnese dialect. Western Acehnese dialects considerably vary when compared to northern dialects. Many studies on Acehnese vowels focused on describing vowels in the Pase dialect. Little attention has been given to other dialects and let alone, vowel variation within those dialects. The current study aims to investigate vowel variation produced by Acehnese in Aceh Barat for the words commonly produced as /ʌ/ in the northern dialect. Six language consultants are recorded reading five Acehnese words containing /ʌ/ vowel in a carrier sentence. Two phonetically trained Acehnese listeners identify the vowel produced based on APA symbols. Formant frequencies of F1 and F2 are generated using Praat software and projected into vowel plots. The findings show that the vowel /ʌ/ is realized as /ə/, /ɛ/, and /ɔ/ by the people in Aceh Barat. Both impression and instrumental analysis seem to agree in terms of vowels realized. The occurrence of the vowel seems to be word-specific instead of location-specific. The word göt is realized as /ə/, /ɛ/, and /ɔ/ while peugöt is only realized as /ə/ and /ɔ/ despite occurring between the same consonants. F2 frequencies are used to produce   /ə/ and /ɔ/ in the word pöt, böh, and röt.